**Show that C _{0}/2 + C_{1}/3 + C_{2}/4 + ......... + C_{n}/n+2 = (1+n.2^{(n+1)})/(n+1)(n+2)**

Please tell me the answer to this question. Need urgently. Help from meritnation experts would be commendable . Please help !

Hi Manish!

Here is the proof of your question.

It is known that: C

_{0}+ C_{1}*x*+ C_{2}*x*^{2}+ C_{3}*x*^{3}+ …. C*= (1+*_{n}x^{n}*x*)^{n}⇒ C

_{0}*x*+ C_{1}*x*^{2}+ C_{2}*x*^{3}+ C_{3}*x*^{3}+ …. C_{n}x^{n}^{ + 1}=*x*(1+*x*)^{n} Let

*z*= 1 +*x*⇒

*d**z*=*dx*When

*x*→ 0,*z*→ 1When

*x*→ 1,*z*→ 2Thus from equation (1)

Hope! You got the proof

Cheers!

**
**